Effect of Interplanetary Magnetic Field on Hemispheric Asymmetry in Ionospheric Horizontal and Field‐Aligned Currents During Different Seasons. Issue 10 (14th October 2021) - Workayehu, A. B.; Vanhamäki, H.; Aikio, A. T.; Shepherd, S. G.
Abstract: We present a statistical investigation of the effects of interplanetary magnetic field (IMF) on hemispheric asymmetry in auroral currents. Nearly 6 years of magnetic field measurements from Swarm A and C satellites are analyzed. Bootstrap resampling is used to remove the difference in the number of samples and IMF conditions between the local seasons and the hemispheres. Currents are stronger in Northern Hemisphere (NH) than Southern Hemisphere (SH) for IMF B y + in NH (B y − in SH) in most local seasons under both signs of IMF B z . For B y − in NH (B y + in SH), the hemispheric difference in currents is small except in local winter when currents in NH are stronger than in SH. During B y + and B z + in NH (B y − and B z + in SH), the largest hemispheric asymmetry occurs in local winter and autumn, when the NH/SH ratio of field aligned current (FAC) is 1.18 ± 0.09 in winter and 1.17 ± 0.09 in autumn. During B y + and B z − in NH (B y − and B z − in SH), the largest asymmetry is observed in local autumn with NH/SH ratio of 1.16 ± 0.07 for FAC. We also find an explicit B y effect on auroral currents in a given hemisphere: on average B y + in NH and B y − in SH causes larger currents than vice versa. The explicit B y effect on divergence‐free current during IMF B z + is in very good agreement with the B y effect on the cross polar cap potential from the Super Dual Auroral Radar Network dynamic model except at SH equinox and NH summer. Key Points: Hemispheric asymmetry in auroral currents is larger for interplanetary magnetic field (IMF) B y + in the Northern Hemisphere (NH) (B y − in the Southern Hemisphere [SH]) than vice versa during both signs of IMF B z Strongest asymmetry occurs in local winter and autumn for B y + in the NH (B y − in the SH) and IMF B z + with NH/SH field aligned current ratio of about 1.18 IMF B y + in the NH and B y − in the SH causes larger auroral currents than vice versa. Effect is stronger for IMF B z + than for IMF B z −